MAPPING FREQUENCY OF OIL SPILLS IN THE CASPIAN SEA USING SENTINEL-2 OPTICAL IMAGES - Sh. Zhantayev, Zh.; Chepashev, D.V.; Kaldybaev, А.А.; Nurakynov, S.M.; Ungarov, K.M. (Academic Scientific Journal of Computer Science, 2020)
The main goal of this work is to evaluate the capabilities of optical images in the problem of detecting oil spills, testing them in the task of mapping zones with a high frequency of oil spills during one year. Using SAR imagery, sometimes it is difficult to separate anthropogenic oil spills and false targets, usually called “look-alikes”. Using optical images for oil spill detection, we rely on the spectral characteristics of objects, and although the reflectivity varies depending on the thickness and composition of the slick, in most cases, oil spills can be distinguished from “look-alikes”. The region near Absheron peninsula was selected as a study area. Optical images of the Sentinel-2 (A, B) satellites were used to detect oil spills and calculate the zones of their most frequent occurrence. Object based approach was chosen for segmentation and classification images. The map of hot spots with high frequencies of oil spills during 2019 year was presented in this article. Conclusions about the advisability of using optical images along with radar data for monitoring oil spills were made.